Freedom and Neighbourhood: Reflecting on the Example of Fred Dewey - Kasper, Rafael; Dewey, Fred; Heuer, Wolfgang; Spaid, Sue; Paquay, JF; Petropoulos, Renée; Petropoulos-White, Pilar; Kohn, Jerome; Gaynor, Fergal; Mahrdt, Helgard (HannahArendt.net, 2023)
ContentPrivate and Public Memories of Fred DeweyRafael KasperGeneral Public - A Fable of SanctuaryFred DeweyGeneral Public – Eine Fabel von einem (un-)geschützen OrtFred DeweyFred und wirWolfgang HeuerFred and usWolfgang HeuerMemoriesSue SpaidErinnerungenSue SpaidMemoriesJF PaquayMemoriesRenée PetropoulosThe Twelve Mortal MenPilar Petropoulos-WhiteHannah Arendt on Being Human and Political PowerJerome Kohn‘Touch With Your Hands His Things’Fergal GaynorIn memoriam Fred DeweyHelgard Mahrdt